3 - Globalisation and Industrial Performance in Nigeria: 10.4314/ad.v28i2.22176 - Onyeonoru , Ifeanyi (Africa Development, 2003)
This paper examines the impact of the neo-liberal globalisation of African economies on industrial performance in Nigeria. Evidence from the study indicates that, contrary to claims by the World Bank, the economic performance of firms in the manufacturing sector during the globalisation period in the study was adversely affected by the process. The study confirms the position that the globalisation project that aims at the structural economic transformation of modern capitalist relations in Africa is associated with a process of de industrialisation. On the basis of conclusions from the study, the author highlights critical lessons for African countries - the need to be critical in the implementation of the IMF/World Bank open-economy, and the 'hands off market-driven, non interventionist development model premised on Adams Smith's 'invisible hand'.